Effectiveness and safety of cold versus hot snare polypectomy: A meta‐analysis. Issue 1 (26th September 2018) - Qu, Junyan; Jian, Haixu; Li, Lixiang; Zhang, Yan; Feng, Bingcheng; Li, Zhen; Zuo, Xiuli
Abstract: Background and Aim: Removal of neoplastic polyps is important for colorectal cancer prevention. The primary aim was to compare the complete resection rate of diminutive (≤ 5 mm) or small colorectal polyps (6–10 mm) using cold snare polypectomy (CSP) versus hot snare polypectomy (HSP). Methods: To April 2018, databases of Medline, EMBASE, Cochrane Central Register of Controlled Trials, and Web of Science were searched for randomized controlled trials comparing CSP and HSP for diminutive or small colorectal polypectomy. Two authors independently assessed trial quality and extracted data. We contacted study authors for additional information. We used the Mantel–Haenszel method for binary endpoints and inverse variance method for continuous outcomes. Subgroup analysis was conducted to explore sources of heterogeneity. Results: Twelve trials involving 2481 patients and 4535 polyps were analyzed. Regarding complete resection rate, there was no statistical significance between CSP and HSP (odds ratio [OR] 0.86, 95% confidence interval [CI] 0.60–1.24). CSP shows more immediate bleeding cases than HSP in per‐lesion analysis while no statistical significance in bleeding needing treatment (OR 1.99, 95% CI 0.59–6.75). In terms of all adverse events, both per‐lesion and per‐patient analysis revealed no difference (OR 1.49, 95% CI 0.87–2.56 and 0.57, 0.11–2.97, respectively). As far as post‐polypectomy bleeding is concerned, there was also no statistical significance between CSP and HSP. Regarding procedure time, CSP was superior to HSP (standard mean difference −1.04, 95% CI −1.22 to −0.87). Conclusions: Cold snare polypectomy is a safe, efficient, and effective polypectomy technique for diminutive or small colorectal polyps.